Cover Image, Volume 28, Issue 1. Issue 1 (16th January 2019) - Beaupin, Lynda K.; Pailler, Megan E.; Brewer‐Spritzer, Erin; Kishel, Eric; Grant, Pei C.; Depner, Rachel M.; Tenzek, Kelly E.; Breier, Jennifer M.
Abstract : The cover image, by Lynda K. Beaupin et al., is based on the Clinical Correspondence Photographs of meaning: A novel social media intervention for adolescent and young adult cancer patients, https://doi.org/10.1002/pon.4896 .